Cross-platform analysis of atrial fibrillation scientific videos: using composite index and a basic assessment scale - Luo, Chong; Qin, Xiaoli; Xie, Xiaoyu; Gao, Jie; Wu, Yuwei; Liang, Weitao; Wu, Zhong (Frontiers in Public Health, 2025)
BackgroundCurrently, video platforms were filled with many low-quality, uncensored scientific videos, and patients who utilize the Internet to gain knowledge about specific diseases are vulnerable to being misled and possibly delaying treatment as a result. Therefore, a large sample survey on the content quality and popularity of online scientific videos was of great significance for future targeted reforms.ObjectiveThis study utilized normalization data analysis methods and a basic assessment scale, providing a new aspect for future research across multiple platforms with large sample sizes and for the development of video content quality assessment scales.MethodsThis cross-sectional study analyzed a sample of 331 videos retrieved from YouTube, BiliBili, TikTok, and Douyin on June 13, 2024. In the analysis of atrial fibrillation scientific videos across four social media platforms, comprehensive metrics and a basic scoring scale revealed associations between platforms, creators, and the popularity and content quality of the videos. Data analysis employed principal component analysis, normalization data processing, non-parametric tests, paired t-tests, and negative binomial regression.ResultsAnalysis of the user engagement data using a composite index revealed a significant difference in the popularity of videos from publishers with a medical background (z = −4.285, p < 0.001), no aforementioned findings were found among video platforms, however, except for the Bilibili platform. As for content quality, while the difference in the total number of videos between the two groups was almost 2-fold (229:102), the difference in qualified videos was only 1.47-fold (47:32), a ratio that was even more unbalanced among the top 30% of videos with the most popularity. Notably, the overall content quality of videos from publishers without a medical background was also significantly higher (z = −2.299, p = 0.02).ConclusionThis analysis of atrial fibrillation information on multiple social media platforms found that people prefer videos from publishers with a medical background. However, it appeared that these publishers did not sufficiently create high-quality, suitable videos for the public, and the platforms seemed to lack a rigorous censorship system and policy support for high-quality content. Moreover, the normalized data processing method and the basic assessment scale that we attempted to use in this study provided new ideas for future large-sample surveys and content quality review.